SEMI-HOMOMORFISMA BCK-ALJABAR - A, Deffyana Prastya; suryoto, suryoto (MATEMATIKA, 2010)
A BCK-algebra is one of the algebraic structure generated over an abelian group. So that, some concepts in group also can be found this structure, for instance, if at a group we have a homomorphism, then at the BCK-algebras we also have a homomorphism, exactly a homomorphism of BCK-algebras. In this paper we discussed a semi-homomorphism of BCK-algebara as generalization of a homomorphism of BCK-algebras. It can be shown every homomorphism of BCK-algebras is a semi-homomorphism of BCK-algebras, conversely not true. By utilizing concept of ideal of BCK-algebras can be proved a semi-homomorphism of BCK-algebras is a homomorphism of BCK-algebras.